Human Resources Performance of Bank Services Reviewed from Strengthening Competence, Enforcing Discipline, and Providing Motivation - Suharni, S.; Dg. Maklassa; Rizal, Samsul (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of Competence and Work Discipline on Employee Performance Through Motivation as an Intervening Variable at Bank Bri Masamba Branch Office. Data collection techniques involved distributing questionnaires and analyzing the data using Amos. The type of research used in this study is quantitative, with questionnaires serving as the primary data. The location of the study was conducted at the Bri Masamba Branch Office, with a population of all permanent employees of the Bri Masamba Branch Office. This study used 111 respondents. Data analysis in this study is descriptive statistical analysis, inferential statistical analysis with path analysis. The results of the study indicate that: competence has an influence on motivation, work discipline has an influence on motivation, competence has an influence on employee performance, work discipline has an influence on employee performance, motivation has an influence on employee performance, competence has an influence on employee performance through motivation, work discipline has an influence on employee performance through motivation. Based on the results of the Sobel test, the findings indicate that Motivation can mediate the influence of Competence and work discipline on employee performance.